Anulabilidade da convenção arbitral pelos vícios de erro e dolo - Tannuri, Rodrigo (2021)
This dissertation seeks to analyze the possibility of applying the causes for nullity of the legal transaction to the arbitration agreement. In order to achieve this end, two causes for nullity will be explored, namely, error and malice, both provided for in art. 171 of the 2002 Brazilian Civil Code. Drawing from definitions of legal transaction and arbitration agreement based on Brazilian and foreign legislation and doctrine, a position will be taken regarding the characterization of the arbitration agreement as a legal transaction. Following, the application of the causes of nullity of the legal transaction to the arbitration agreement will be assessed through practical examples and hypothetical cases to provide a better understanding of the topic. In addition, the effects of the nullity of the arbitration agreement, in view of the autonomous theory of the arbitration agreement will be examined. The need to preserve the legal transaction whenever nullity hypotheses provided for in the Brazilian Civil Code are secured will be also addressed. Under this approach, it will be further investigated if it would be up to the arbitrator or the judge the responsibility for analyzing the nullity of the arbitration agreement. Finally, a position will be presented regarding the application of the causes of nullity of the legal transaction to the arbitration agreement, setting forth, as far as possible, the effects of such nullity and who would be responsible for its assessment